(untitled) (Annals of Medical Research, 2021)
Aim: Although, bosentan and sildenafil have been used to treat PAH, the effect of these drugs on electrocardiographic (ECG) changes are still unclear. The aim of this study is to evaluate the effects of bosentan, sildenafil, and their combination on T-wave amplitude and QT interval in rats with monocrotaline (MCT)-induced PAH.